Galaxy kinematics and mass calibration in massive SZE-selected galaxy clusters to z = 1.3. Issue 1 (1st October 2018) - Capasso, R; Saro, A; Mohr, J J; Biviano, A; Bocquet, S; Strazzullo, V; Grandis, S; Applegate, D E; Bayliss, M B; Benson, B A; Bleem, L E; Brodwin, M; et al.
Abstract: The galaxy phase-space distribution in galaxy clusters provides insights into the formation and evolution of cluster galaxies, and it can also be used to measure cluster mass profiles. We present a dynamical study based on ∼3000 passive, non-emission-line cluster galaxies drawn from 110 galaxy clusters. The galaxy clusters were selected using the Sunyaev–Zel'dovich effect (SZE) in the 2500 deg 2 South Pole Telescope (SPT)–SZ survey and cover the redshift range 0.2 <z < 1.3. We model the clusters using the Jeans equation, while adopting NFW mass profiles and a broad range of velocity dispersion anisotropy profiles. The data prefer velocity dispersion anisotropy profiles that are approximately isotropic near the centre and increasingly radial toward the cluster virial radius, and this is true for all redshifts and masses we study. The pseudo-phase-space density profile of the passive galaxies is consistent with expectations for dark matter particles and subhaloes from cosmological N -body simulations. The dynamical mass constraints are in good agreement with external mass estimates of the SPT cluster sample from either weak lensing, velocity dispersions, or X-ray Y X measurements. However, the dynamical masses are lower (at the 2.2σ level) when compared to the mass calibration favoured when fitting the SPT cluster data to a Λcold dark matter model with external cosmological priors, including cosmic microwave background anisotropy data from Planck . The discrepancy grows with redshift, where in the highest redshift bin the ratio of dynamical to SPT + Planck masses isη = 0.63^+0.13_-0.08± 0.06 (statistical and systematic), corresponding to a 2.6σ discrepancy.